THE INFLUENCE OF DESTINATION IMAGES ON REVISIT INTENTION IN MOUNT BATUR - Ni Ketut Wiwiek Agustina (Institut Pariwisata dan Bisnis Internasional, 2018)
Tourism has become one of idol business in Indonesia, which can be seen by the graph of performance continues to rise up compared to oil, gas, coal, and palm oil which continue to decline. Each destination tries to serve tourists better using many kinds of strategies, one of them is the destination image. This research aims to analyze the influence of destination image on the revisit intention in Mount Batur, Bali. The study is explanatory and done using quantitative and descriptive approaches. The number of samples to be used is 100 samples. The method of data collection is done by questionnaire collection method to analyze the influence of the destination image variable on the variable of revisit intention obtained by descriptive explanation. Based on the results of the research conducted, it shows that the image of the destination has a significant effect on the interest in returning to tourists in Mount Batur, which means that the hypothesis proposed in the study was accepted. This can be seen in the results of the hypothesis test the value of t arithmetic obtained is equal to 7.242 with a significance value of 0.000 smaller than 0.05. Based on the correlation test, the relationship between the two variables is at a moderate level with a percentage of influence of 34.9%. So that from this it is expected that tourists area managers of Mount Batur must try to maintain security, comfort and the environment.